The history of entrepreneurship in Mexico: A view from the academic lens - Montiel, Oscar (Emerald Publishing Limited, 2020)
he legitimacy of history: dictated Bloch. Today, in many areas of knowledge, and of course in entrepreneurship (Wadhwani, 2010), it has become superlative. The aim of this chapter is analyzing the literature about entrepreneurship in Mexico mainly from the last 11 years of studies on the subject. Through this review, we want to highlight the progress in the field, as well as deeper opportunities in its research as a result of it, the profound need for incorporating them not only in the national academic debate but also into the entrepreneurship ecosystem and in specific public policies.